2011
DOI: 10.1111/j.1442-9071.2011.02664.x
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and retinal support of a foldable capsular vitreous body injected with saline or silicone oil implanted in rabbit eyes

Abstract: Introduction: The aim of this study was to evaluate over a 180-day period the biocompatibility and retinal support of a foldable capsular vitreous body injected with either saline or silicone oil implanted in rabbit eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…In our previous study28, we found that most of FCVB-implanted eyes developed cataracts after a long-term tamponade. In order to better observe fundus, we had to perform lensectomy which lead to secondary lesion.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…In our previous study28, we found that most of FCVB-implanted eyes developed cataracts after a long-term tamponade. In order to better observe fundus, we had to perform lensectomy which lead to secondary lesion.…”
Section: Discussionmentioning
confidence: 78%
“…In the PVA + FCVB group, lensectomy was performed during par plana vitrectomy (PPV) surgery. Our prior study28 revealed that severe cataracts occurred most frequently in FCVB implantated eyes and that this led to a failure to observe the fundus. In order to avoid lesions from a second surgery, the lens and vitreous were removed at the same time during vitrectomy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was designed by simulating the shape of the natural human natural vitreous cavity, possesses excellent mechanical properties, optical properties and biocompatibility, and can adequatelymaintain the shape and intraocular pressure of the eyeball, thus avoiding the risk of repeated replacement of silicone oil and eyeball removal [4] , the complications of silicone oil associated withlong-term compression of the retina, and does not require the placement of patients in special positions, such as the prone position, after the operation. The safety and efficacy of FCVB were initially confirmed through a series of animal studies, a standard process priorto clinical trials [5][6][7] . However, the clinical applications of FCVB havenot been verifiedyet, and the number of previous studies has also been relatively small.…”
Section: Introductionmentioning
confidence: 99%